Gestão da produtividade e qualidade de vida dos analistas de controle externo: uma avaliação do programa de teletrabalho no Tribunal de Contas do Estado do Ceará - Duarte, Lucas de Sousa (2024)
The conflict between the increasing demands of public administration and citizens' right to a reasonable duration of legal processes has prompted the emergence of various public policies in management and labor areas aimed at enhancing productivity, directly impacting public servants. Therefore, this research aimed to evaluate the Telework Program of the State Court of Audit of Ceará since its implementation in 2018 until 2024. The program was developed due to a backlog of ongoing cases within the organization, with the goal of understanding its implications on the quality of life of external control analysts. To achieve this, an analysis of the official regulations supporting the program and its creation context was conducted, alongside surveys and interviews with participating employees. These analyses were grounded in the principles of In-Depth Evaluation (Rodrigues, 2008, 2011), seeking a comprehensive understanding of the program from the viewpoint of its participants. The results indicated that the Telework Program emerged in a complex context where the institution faced a growing need to increase the production of inspection reports to manage its caseload. Simultaneously, it absorbed responsibilities, structure, and resources from another public entity, the Court of Audit of Municipalities, which was being dissolved and had an initial telework program. Additionally, the Covid-19 pandemic necessitated emergency changes that served as learning experiences to finalize the program's main regulations from 2021 onwards. Ultimately, it was observed that employees experiencing telework perceive significant and positive impacts on their quality of life, as it provides flexibility and autonomy over their time, allowing for a balance between professional and personal activities, despite concerns about increased targets for program participants.